Nationwide seroprevalence of antibodies to SARS-CoV-2 in asymptomatic population in South Korea: a cross-sectional study - Eun-Hee Nah; Seon Cho; Han-Ik Cho; Hyeran Park; Inhwan Hwang (BMJ Open)
Objective Asymptomatic active infection might be an important contributor to the COVID-19 outbreak. Serological tests can assess the extent of exposure and herd immunity to COVID-19 in general populations. This study aimed to estimate the nationwide seroprevalence of SARS-CoV-2 antibodies according to age, sex and clinical status in South Korea.Design, setting and participants This cross-sectional study randomly selected health examinees who underwent health check-up at 16 health promotion centres in 13 Korean cities across the country between late September and early December 2020. Residual serum samples were obtained from 4085 subjects (2014 men and 2071 women). Antibodies to SARS-CoV-2 were measured by electrochemiluminescence immunoassay using Elecsys Anti-SARS-CoV-2 (Roche Elecsys, Mannheim, Germany).Primary and secondary outcome measures Fisher’s exact test was used to compare the seroprevalence according to sex, age group and region. The relative risks of being seropositive according to the characteristics of the study subjects were analysed using logistic regression analysis.Results The overall seroprevalence of anti-SARS-CoV-2 was 0.39% (95% CI=0.20% to 0.58%): 0.30% (95% CI=0.06% to 0.54%) for men and 0.48% (95% CI=0.18% to 0.78%) for women. The rate of anti-SARS-CoV-2 positivity varied significantly between different regions of Korea (p=0.003), but not with age group, sex, or the statuses of obesity, diabetes, hypertension or smoking.Conclusions Most of the Korean population is still immunologically vulnerable to SARS-CoV-2, but the seroprevalence has increased relative to that found in studies performed prior to September 2020 in Korea.